Early Warning System of Cervic Cancer (EWS Ca. CERVIC) In Women of Reliable Age Based on Mobile - Aprina Aprina; Titi Astuti; Gustop Amatiria (Universitas Aisyah Pringsewu, 2022)
Cervical cancer is cancer with the highest prevalence in Indonesia. In the form of an application for early detection of cervical cancer risk so that the Cervical Cancer Early Warning System (EWS Ca Cervical) can perform early detection of cervical cancer and can provide solutions regarding appropriate early prevention and can assist the public in recognizing risk factors for cervical cancer in women of childbearing age and make it easier for people to use this application. This research aims to obtain a model of an early detection system for Ca. The cervix in women of childbearing age is mobile-based. This type of research is an observational analytic study with an analytical research design with a cross-sectional approach. The measuring instrument for data collection is a questionnaire for primary data obtained during the research. The research will be conducted from April to December 2022. The research will be conducted in Lampung Province. The population of this study was all women of childbearing age. The sample size in this study was 388 samples with random sampling data collection techniques. Data analysis with a univariate analysis method was carried out descriptively and for bivariate analysis using Chi-Square statistical test, with a 95% confidence degree, for multivariate analysis using a logistic regression test. The results showed that there was a relationship between education, age, age at first having sex, the pattern of sexual intercourse, parity, personal hygiene and use of panty liners, smoking, oral contraceptives, nutritional deficiencies, socioeconomic status, sexual partners, history of venereal disease and the risk of cervical cancer, the results of data processing on the ISO 25010 test by testing two aspects, namely functional suitability and usability, stated that the EWS Ca Cervical application software had an overall percentage of applications getting a score of 88% which means the application is good to use, it is hoped that this application will be an early intervention used in women childbearing age can be carried out more effectively and efficiently so that women can prevent cervical cancer early.